Updated review on diagnosis of Helicobacter pylori - R. Ugiagbe; S. Smith (Microbiota in Health and Disease)
This review gives an overview of the main articles published in the field of Helicobacter pylori (H. pylori) diagnosis in the past year from April 2023-March 2024. The main themes include invasive and noninvasive diagnostic methods of H. pylori, newer methods, such as a panel of ten H. pylori specific antibodies test, testing for H. pylori using gastric fluid and outer membrane protein-cell receptor reactions diagnostic methods, and serological and pepsinogen tests. Others are Latex Agglutinin Turbidity assay and PyloPlus Urea Breath Test validations, as well as artificial intelligence cost-effectiveness. Enhanced endoscopic and histopathological diagnosis also featured Computer Assisted Diagnosis systems and H. pylori deep learning models. Molecular diagnostic techniques include H. pylori reflexive stool testing, whole genomic sequencing as well as PCR diagnostics and clarithromycin resistance testing.